The influence of risk perception on mutual fund investment interest in management study program students - Baharuddin, Aris; Praditya, Andi Wira; Syarifuddin, Syarifuddin (Universitas Negeri Makassar, 2024)
This study aims to determine the partial effect of risk perception on mutual fund investment interest. The research employs a descriptive quantitative approach. The researcher used data collection techniques through questionnaires, observation, and documentation to achieve this objective. The sample consisted of 85 respondents. Data analysis was conducted using SPSS Statistics software version 29, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination test. The results indicate that the indicators used for each variable—risk perception and mutual fund investment interest—are categorized as good. The significance test results show that risk perception has a significant effect, with a p-value smaller than the alpha value and the calculated t-value exceeding the critical t-table value. Thus, it can be concluded that risk perception significantly affects mutual fund investment interest among students of the 2022 Management Study Program at Universitas Negeri Makassar.